Tradução, adaptação transcultural e validação do Spinal Cord Injury Pain Instrument (SCIPI) para o português brasileiro - CACERE, Marcela (2021)
Introduction: Pain promotes considerable interference in the lives of people with spinal cord injury sequelae, with neuropathic pain is one of the most prevalent. Discrimination of the mechanisms of pain and an assessment tool that takes into account the characteristics of the spinal cord injury offers a better management of this condition. Objective: To carry out the translation, cross-cultural adaptation and validation for Brazilian Portuguese of the Spinal Cord Injury Pain Instrument (SCIPI). Methods: The SCIP was translated and cross-cultural adapted, with the pre-final version being applied to 10 patients with sequelae of spinal-cord injury and who had pain reports. The final version of SCIPI was applied to 100 patients. The domains of the measurements evaluated were: structural validity through factor analysis; test-retest reliability; construct validity through correlations with the Douleur Neuropathique 4 (DN4) questionnaires and the Leeds Neuropathic Pain Assessment Questionnaire (LANSS); diagnostic accuracy through the ROC curve. Results: No item in the pre-final version of the questionnaire presented problems of comprehension by more than 20% of patients, thus resulting in the final version of SCIPI. Good adjustment indexes were found in the confirmatory factor analysis (chi-square/degrees of freedom = 0.808; Comparative Fit Index = 1,000; Tucker Lewis Index = 1,000; Root Mean Square Error of Approximation (90% confidence interval) = 0.000 (0.000 to 0.187); Standardized Root Mean Square Residual = 0.061). There were significant correlations between SCIPI and DN4 (rho = 0.546) and LANSS (rho = 0.295). SCIPI showed good reliability (CCI = 0.89), EPM was 0.40 and moderate diagnostic accuracy (AUC = 0.860). Conclusion: The translated and adapted Brazilian version of SCIPI has adequate measurement properties, consequently, it can be used in a clinical setting and in research to measure neuropathic pain related to spinal-cord injury.